UV-B RADIATION INDUCED CHANGES IN PHOTOSYSTEM II PHOTOCHEMISTRY OF THE THYLAKOID MEMBRANES FROM PRIMARY LEAVES OF BARLEY - S. D. SUDHEER,; S. ADAM,; S. D. S. MURTHY, (The Bioscan, 2011)
Exposure of UV-B radiation (25-100 μ moles) induced inhibition in both whole chain electron transport as well as PS II photochemistry in a intensity dependent manner. The probable site of inhibition in PS II catalyzed electron transport could be water oxidation complex. To confirm this, an artificial donor, Diphenylcarbazide has been used and methyl viologen is employed as an acceptor. The above electron transport measurements clearly demonstrated that water oxidation complex is main target for the action of UV-B radiation.